If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7a + 16 + -3a = -44 Reorder the terms: 16 + 7a + -3a = -44 Combine like terms: 7a + -3a = 4a 16 + 4a = -44 Solving 16 + 4a = -44 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 4a = -44 + -16 Combine like terms: 16 + -16 = 0 0 + 4a = -44 + -16 4a = -44 + -16 Combine like terms: -44 + -16 = -60 4a = -60 Divide each side by '4'. a = -15 Simplifying a = -15
| 9+10a=10 | | (x-2)=3(x-3) | | (X)=2(1+3) | | 2(4x-15)=3(x+15) | | 3+3p=6 | | 4a+12=7 | | 4(x-9)=x-15 | | 4(y-8)=8 | | m/3-6 | | 8h^2-50= | | 4/9:134/72 | | 9+3y-2yt=14 | | x(2x+7)= | | 11-8b=-5-4b | | 4a+12=-16 | | 4(y-4)=2(y+25)-4 | | 10x-18=x+63 | | 5Y+9=8Y-6 | | -8+9n=10 | | 7m-6=-104 | | 7x+60=x+60 | | (4x^2+4x+1)-(4x^2+2)=8x+16 | | 3-(5x-1)/10=(x-1)/5-(x-3)/2 | | 5r=-1 | | 5r=-2 | | 7-6a=1-4a+a | | 4u+13=65 | | 4p-4=56 | | 9x-90=4x+55 | | A=49sqin | | 5(x-5)+5=-50 | | 6b+3=4b+5 |